Targeting cellular senescence in cancer and aging: roles of p53 and its isoforms. (3rd July 2020) - Beck, Jessica; Turnquist, Casmir; Horikawa, Izumi; Harris, Curtis
Abstract: Cellular senescence and the associated secretory phenotype (SASP) promote disease in the aged population. Targeting senescent cells by means of removal, modulation of SASP or through cellular reprogramming represents a novel therapeutic avenue for treating cancer- and age-related diseases such as neurodegeneration, pulmonary fibrosis and renal disease. Cellular senescence is partly regulated by the TP53 gene, a critical tumor suppressor gene which encodes 12 or more p53 protein isoforms. This review marks a significant milestone of 40 years of Carcinogenesis publication history and p53 research and 15 years of p53 isoform research. The p53 isoforms are produced through initiation at alternative transcriptional and translational start sites and alternative mRNA splicing. These truncated p53 isoform proteins are endogenously expressed in normal human cells and maintain important functional roles, including modulation of full-length p53-mediated cellular senescence, apoptosis and DNA repair. In this review, we discuss the mechanisms and functions of cellular senescence and SASP in health and disease, the regulation of cellular senescence by p53 isoforms, and the therapeutic potential of targeting cellular senescence to treat cancer- and age-associated diseases. Abstract : A review of the mechanisms and functions of cellular senescence in development, aging and cancer focusing on its regulation by p53 isoforms and the therapeutic potential of targeting cellular senescence and SASP to treat cancer- and age-associated diseases.